DIAGNOSIS OF CONGENITAL CMV IN THE ANTENATAL PERIOD - Daminov F. A.; Djabbarova N. R.; Rustamova Sh. S. (Web of Journals Publishing, 2025)
Antenatal diagnosis of congenital CMV infection is based on the detection of primary CMV infection in a pregnant woman, reactivation of latent or superinfection with a new strain of CMV (B). The standard of examination of a pregnant woman is the determination of specific antibodies of Ig M and Ig G classes, Ig G avidity in serum by enzyme-linked immunosorbent assay (hereinafter referred to as ELISA) or immunochemiluminescence assay (hereinafter referred to as CLIA), performed initially at the diagnosis of pregnancy [19,20,21,22].
Keywords: Pregnancy, cytomegalovirus infection, new strain, diagnosis, superinfection, laboratory diagnosis.